A Gender Assessment of Mumbai's Public Transport - World Bank (Washington, DC, 2013)
This report provides: a high-level understanding on women's travel patterns that builds the foundation for understanding the ways in which they use public transport and the degree to which this is met by the public transport systems; and a first-cut view on women's priorities in public transport and potential ideas for addressing them. The purpose of this report is to initiate a dialog on these questions and begin to develop a picture of the role transport currently plays in women's lives with an understanding of the further role it can play, given women's specific needs. This study was carried out in Mumbai. Mumbai, formerly known as Bombay, is the capital of the Indian state of Maharashtra and is the commercial and entertainment capital of India. Throughout this report the authors has used the term 'women' to refer to women and girls above the age of 16 as several of our survey respondents are students between the ages of 17 and 21. However, there is a need for a deeper understanding of the public transport needs of school- children; many of them use public transport to go to better schools that are father away from their homes. The study was on public buses and trains, however, other modes of public transport available in the city but not included in the study are black and yellow metered taxis and auto- rickshaws.